PENGARUH SUHU PENGERINGAN GRANUL KOMBINASI MINYAK SERAI DAPUR - DAUN JERUK PURUT TERHADAP JUMLAH KEHILANGAN MINYAK DAN AKTIVITAS LARVASIDANYA - Sri Mulyani; Annisa Khoiri Z.; M. Syafii Nusri (Majalah Obat Tradisional, 2016)
Granules of lemongrass and kaffir lime oil are reported to have larvicidal activity against the mosquito Aedes aegypti, with LC50 of 38.30ppm and 39.58ppm, while LC90 of 51.57ppm and 79.43ppm respectively. During the manufacture of granules, loss of oil are reported by 64.20% to 65.91% for lemongrass and kaffir lime oil. This research aims to make granules combination from lemongrass and kaffir lime oils by varying the temperature of the drying granules and testing its larvicidal activity against Ae. aegypti. Oil combination is selected by using analysis simplex lattice design, and the combination chosen is made of granules, in drying room temperature for 24h, a temperature of 50°C for 2h 30min and a temperature of 70°C for 1h. Larvicidal activity testing against larvae of Ae. aegypti is done by using the third instar larvae 20 for each granule solution made in 5 series of concentration, and left exposed for 24h. The number of deaths of larvae is calculated and analyzed by modified probit analysis Finney to determine LC50 and LC90. The results showed the combination lemongrass-kaffir lime oil is selected ratio of 9:1, and drying the granules with a temperature of 70°C for 1h produces the greatest larvicidal activity with 63.17ppm LC50 and LC90 of 85.04ppm.